Heavy metal distribution, mobility and risk assessment in surface sediment of Sungai Puloh in Selangor, Malaysia - Abubakar, Usman Sadiq (2018)
Sungai Puloh is a mangrove swamp area plagued with industrial, agricultural and other commercial activities and has a direct small link to the straits of Malacca. It is surrounded by industries including steel and paint manufacturing companies, car repair shops etc. Heavy metals (HMs) are environmental pollutants whose sources are both natural and anthropogenic. Heavy metals bioavailability and mobility is affected by physical, chemical and biological factors among which are organic matter and sediment characteristics. Organic matter and particle size distribution play a significant role in the fate of HM in the sediment, and consequently the river. The aims and objectives therefore, are to investigate the concentration of some selected HMs (Cu, Zn, Ni, Cd and Pb) in the surface sediment of Sg. Puloh, determine organic matter content and particle size distribution as well as assess the degree of HM contamination/risk by means of pollution indices evaluation namely: risk assessment code (RAC), geoaccumulation Index (Igeo), contamination factor (CF) and pollution load index (PLI). Sequential extraction technique SET and Aqua regia digestion were performed using Atomic Absorption Spectrophotometer (AAS) (Perkin Elmer 800) for heavy metal concentration. Loss on ignition and pipette method of analyses were employed for the determination of organic matter content and particle size respectively. SPSS statistical package version 22 was used to determine correlation, significance or otherwise of heavy metals concentration. Heavy metals concentrations for Cu, Zn, Ni, Cd and Pb were found between 83.05-202.34, 405.39-755.04, 114.67-226.90, 0.53-3.06 and 95.19-225.47 μg/g respectively. Grain size analysis revealed clay in the sediment at between 52.89-60.16, silt 25.38-35.99 and sand 4.68-14.42%. Organic matter content ranged between 38.45-46.90%. Correlation between grain size and total metal concentration revealed was significant for Cd, Cu, and Ni (r = 0.657*, r = 0.705* and r = 0.682*) respectively. Kruskal Wallis’ nonparametric test revealed significant difference in heavy metals concentrations (P < 0.01, P < 0.05). Risk assessment code RAC showed medium (RAC= 11-30) to very high risk (RAC > 50) with Pb posing the highest risk. Geoaccumulation index, Cd highest in S5 (Igeo) = 3 while Cu lowest (Igeo)= 0.2 in S2. Contamination factor (CF), Zn and Pb highest, Ni and Cu lowest. Pollution load index showed values greater than 1 (PLI > 1), indicating high level of pollution. Sediment of Sg. Puloh has high contamination of HM and the source are both from natural and anthropogenic. The presence of heavy metals in the residual fraction confirms that some of the heavy metals come from natural source. From the result obtained, it can be concluded that Sg. Puloh is highly polluted. All the stations have shown high level of heavy metal concentration from both natural and anthropogenic sources, high organic matter content from a sediment that is characteristically clay. Pollution indices have also indicated high contamination, especially in S5, S3 and S4. This can be attributed to the cited industries nearby, agriculture and other activities.